The Conditions of Achieving Interactive Mindfulness Through Virtual Reality Single User: A Case Study Experience in Macao - Ng, Ka Man (University of Saint Joseph, 2024)
Virtual reality (VR), a computer-generated 3D environment, allows one to navigate and possibly interact, resulting in real-time simulation of one or more of the user’s five senses (M. Gutierrez et al., 2008; Vince, 2004). Despite its history through past decades, this technology has quickly developed recently. Virtual tours and spaces have been widely used in the education, arts, and rehabilitation industries. According to research, it has significant effects on mindfulness (improving mood), cognitive development (better learning ability), and embodiment (relieving pain and medical conditions). This thesis aims to identify the conditions for Macao's single-user experience to achieve mindfulness in virtual reality through immersion and interactivity. With their various definitions, this research uses the two spectrums on the levels of immersion and interactivity, conducts four experiment settings with Macao residents, and collects qualitative questionnaires and quantitative survey data. The four settings differ as they tackle different aspects: spiritual memory, historical memory, aesthetic appreciation, and meditation through concept. The analysed results were then evaluated to seek better conditions for the local community to achieve mindfulness by immersing themselves in virtual reality
Keywords: Single user experience; Thesis and Dissertations PhD in Global Studies (D-GLS); University of Saint Joseph; immersion; interactivity; mindfulness; virtual reality; well-being